Oleic acid enriched diet affects the metabolome composition of the hybrid grouper infected with vibriosis - Natnan, Maya Erna; Low, Chen-Fei; Chong, Chou-Min; Mohd Jasmany, Muhammad Shuhaily; Baharum, Syarul Nataqain (Springer Science and Business Media B.V., 2024)
This study focuses in investigating the fatty acid contents of surviving infected hybrid grouper fed with oleic acid immunostimulant. After a 6-week feeding trial, Epinephelus fuscoguttatus × Epinephelus lanceolatus fingerlings were infected with Vibrio vulnificus. One week after bacterial challenge, fish oil was extracted from body tissue of surviving infected fingerlings using the Soxhlet extraction method. The extracted samples were then sent for GC–MS analysis. The raw GC–MS data were analyzed using software programs and databases (i.e., MetaboAnalyst, SIMCA-P, NIST Library, and KEGG). A total of 39 metabolites were putatively identified, with 18 metabolites derived from the fatty acid group. Our further analysis revealed that most metabolites were highly abundant in the oleic acid dietary samples, including oleic acid (4.56%), 5,8,11-eicosatrienoic acid (3.45%), n-hexadecenoic acid (3.34%), cis-erucic acid (2.76%), and 9-octadecenoic acid (2.5%). Worthy of note, we observed a greater abundance of α-linoleic acid (15.57%) in the control diet samples than in the oleic acid diet samples (14.59%) with no significant difference in their results. The results obtained from this study revealed that surviving infected hybrid grouper expressed more immune-related fatty acids due to the effect of oleic acid immunostimulant. Therefore, in this study, we propose oleic acid as a potential immunostimulant in enhancing fish immunity in aquaculture industry.